2008
DOI: 10.1055/s-0028-1089488
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and HER2 Expression in advanced Biliary Tract Cancer

Abstract: AIM:To analyze the pathogenetic role and potential clinical usefulness of the epidermal growth factor receptor (EGFR) and the human epidermal growth factor receptor 2 (HER2) in patients with advanced biliary tract cancer (BTC). METHODS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…Immunohistochemistry studies have shown that the epidermal growth factor receptor (EGFR) is over expressed in CCA human samples 115,116 . EGFR activation triggers the oncogenic MAPK-ERK signalling pathway in cholangio cytes, making this receptor a potential target for therapy 117 .…”
Section: Growth Factorsmentioning
confidence: 99%
“…Immunohistochemistry studies have shown that the epidermal growth factor receptor (EGFR) is over expressed in CCA human samples 115,116 . EGFR activation triggers the oncogenic MAPK-ERK signalling pathway in cholangio cytes, making this receptor a potential target for therapy 117 .…”
Section: Growth Factorsmentioning
confidence: 99%
“…This pathway is activated by a diverse group of extracellular signals, including growth factor receptors [e.g., EGF receptor (EGFR)]. Expression of EGFR has been validated to be enhanced in tumor samples from 39.2%-46.2% of patients with biliary cancers (6,7). Moreover, activating mutations of KRAS and BRAF can occur in biliary cancers, with reported incidences of 8% to 58% (8) and 0 to 22%, respectively (9), suggesting that activation of the RAF/MAPK signaling pathway may be a key event in a significant proportion of biliary cancers.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Biliary tract cancers express EGFR in 60.7% of cases. (6) The EGFR-overexpressing GBC cases show poorly differentiated histology and decreased survival of 1.5 years in median survival. (7) Amplification and point mutations of the EGFR gene have been reported to be 1% and 15 -26.5%, respectively, in GBC.…”
mentioning
confidence: 99%